Crosslinked cellulose-based dry-state water-absorbing fabric as well as preparation method and application thereof

Through the preparation method of crosslinked cellulose-based dry water-absorbing fabric, the problem of insufficient mechanical properties and water absorption ratio of the existing etherified cellulose hydrogel dressing is solved, and efficient wound dressing materials are achieved.

CN119465616AActive Publication Date: 2025-02-18SOUTH CHINA UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411529205.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-18
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The degree of etherification of existing etherified cellulose hydrogel dressings is uncontrollable in the industrial process, resulting in low mechanical properties and insufficient water absorption rate, which cannot meet the application needs of wound dressings.

Method used

The preparation method of crosslinked cellulose-based dry water-absorbing fabric is adopted, and the etherification and cross-linking of cellulose are controlled to improve water by soaking potassium chloride solution, sodium hydroxide treatment, microwave-assisted etherification and citric acid cross-linking and other steps. Mechanical properties and liquid retention ability of the gel.

Benefits of technology

The stability and mechanical properties of cellulose hydrogels have been improved, and the water absorption rate has been significantly increased. It can form a fibrous hydrogel with good liquid retention ability, mechanical properties and transparency, suitable for all kinds of wound repair scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465616A_ABST
    Figure CN119465616A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of medical materials, and discloses a cross-linked cellulose-based dry-state water-absorbing fabric as well as a preparation method and application thereof. The preparation method comprises the following steps: soaking cellulose base cloth with a potassium chloride solution; washing the cellulose base cloth, and controlling the water content through a padder; carrying out alkalization treatment on the base cloth; carrying out etherification treatment on the base cloth by adopting a microwave-assisted technology; performing crosslinking on the base cloth; and drying to obtain the cross-linked cellulose-based dry-state water-absorbing fabric. The mechanical property and the liquid retention rate of the cellulose-based hydrogel fiber are remarkably improved through cross-linking treatment. The preparation process of the cross-linked cellulose-based dry-state water-absorbing fabric is simple and controllable, and large-scale production is easy to realize; after absorbing liquid, the obtained cross-linked cellulose-based dry-state water-absorbing fabric can quickly form fibrous hydrogel with good liquid retention capacity, mechanical property and transparency, is suitable for various wound repair scenes, and has wide market application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] As the first barrier for physical protection and prevention of microbial invasion, the skin is an indispensable part for ensuring human safety and maintaining life. Intact skin is the first barrier of the human body against the external environment and microorganisms, and it has therefore become the most vulnerable organ. Every year, millions of people suffer skin damage due to some physical and chemical factors or diseases. Traditional dry wound dressings, such as gauze, bandages, and cotton wool, can protect wounds and absorb some exudate, but there are still many defects that are not conducive to wound healing, such as easy adhesion to the wound, secondary damage during dressing changes, and failure to prevent infection. With the progress of society and the development of medical technology, traditional dressings can no longer meet the needs of modern wound treatment when dealing with complex or chronic wounds, and new wound dressings have become the focus of research.

[0002] Studies have shown that in terms of avoiding wound infection, a good moist environment promotes cell adhesion, proliferation, and differentiation, and hydrogels have become ideal materials for wound dressings due to their unique moisture retention and biocompatibility. Early hydrogel dressings were mainly used to absorb wound exudate and provide basic physical protection. Wound healing is a complex process that can be roughly divided into four stages: hemostasis, inflammation, proliferation, and tissue remodeling. With the continuous understanding of these processes, hydrogel dressings have begun to integrate more bioactive ingredients, such as growth factors and antibacterial agents. Modern hydrogel dressings can not only promote wound healing, but also have intelligent responsiveness and can adjust drug release according to changes in the wound environment.

[0003] With the innovation of materials science and the increasing public attention to the concept of sustainable development, hydrogel dressings have shown a significant trend of diversification in material selection. In addition to traditional synthetic polymers, polymers of natural origin have also been widely studied because of their good biocompatibility. In addition, semi-synthetic polymers including carboxymethyl cellulose have good biocompatibility and fluid absorption properties, and have also attracted people's attention.

[0004] Hydrogel fiber is a combination of fabric and hydrogel. If used in the field of wound dressings, it can overcome some of the shortcomings of traditional dressings. Its fibrous characteristics give it a high specific surface area and high air permeability, which helps to provide more effective gas exchange and reduce the humid environment and infection risk around the wound. At the same time, its hydrogel characteristics allow it to maintain a high water content, which helps to maintain the moisture balance on the surface of skin wounds. At the same time, hydrogel wound dressings with high elasticity can adapt to wounds of different shapes and are not prone to damage during use. Therefore, hydrogel fibers that combine the advantages of hydrogel and fiber materials can be well used in the field of wound dressings.

[0005] With the innovation of materials science and the increasing public attention to the concept of sustainable development, hydrogel dressings have shown a significant trend of diversification in material selection. They can be roughly divided into the following three categories: traditional synthetic polymers, natural polymers from natural sources, and semi-synthetic polymers. Regardless of which material is selected, its water absorption, water retention and biocompatibility must be considered when applied in the field of wound dressings.

[0006] Carboxymethyl cellulose (CMC) has many properties such as abundant sources, low price, easy functionalization and good biocompatibility, especially biocompatibility, biodegradability, bioadhesion and tissue similarity, so it has attracted much attention in wound dressing research. The gelation of CMC will maintain the moist environment of the area around the wound and increase the blood viscosity around the wound, thereby improving the hemostatic effect. At present, the gelation of CMC can be achieved through etherification. The solubility of cellulose after etherification changes significantly, and its solubility in water increases. The change in its solubility is related to the degree of substitution, the size of the substituent and the polarity of the substituent. However, in the field of wound dressings, over-etherified cellulose will not be able to maintain its basic morphology in aqueous solution and may even cause some of the etherified cellulose to adhere to the wound, which is very unfavorable for wound recovery.

[0007] The mechanical properties of etherified cellulose hydrogels will drop significantly after absorbing water, which is undesirable in the field of wound dressings. Cross-linking is a commonly used method to enhance the mechanical properties of hydrogels. At the same time, moderate cross-linking can keep the morphology of hydrogels unchanged after absorbing water, which is also beneficial for their application in wound dressings.

[0008] At present, there are many applications for etherified cellulose, but the degree of etherification is uncontrollable in the industrial process, which makes it impossible to stably produce uniform etherified cellulose in large quantities. At the same time, the cellulose etherified by the current method is either unstable in shape, has low mechanical properties, or has insufficient water absorption, which cannot meet the application of wound dressings. Summary of the invention

[0009] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a cross-linked cellulose-based dry absorbent fabric.

[0010] The present invention has a simple preparation process, a short preparation cycle, controllable performance, easy large-scale processing and low cost; the dry absorbent fabric of the present invention can form a fibrous hydrogel with good liquid retention capacity, mechanical properties and transparency after quickly absorbing liquid, and can be applied to various wound repair scenarios.

[0011] Another object of the present invention is to provide a cross-linked cellulose-based dry absorbent fabric prepared by the above method.

[0012] Another object of the present invention is to provide application of the cross-linked cellulose-based dry absorbent fabric in wound dressing materials.

[0013] The purpose of the present invention is achieved through the following solutions: A method for preparing a cross-linked cellulose-based dry absorbent fabric comprises the following steps: (1) soaking the base fabric in a potassium chloride solution, heating it, washing it, and rolling it until the water content is 50wt%-90wt%, to obtain sample a; (2) soaking sample a in a sodium hydroxide solution to react and obtain an alkalized sample b; (3) adding an etherification solution to the alkalized sample b, reacting under microwave assistance, and washing to obtain an etherified sample c; (4) The etherified sample c is immersed in a crosslinking agent solution to react, and the obtained product is washed and dried to obtain a crosslinked cellulose-based dry absorbent fabric.

[0014] The base fabric in step (1) comprises, by mass percentage, 60%-100% cellulose fibers and 0%-40% non-cellulose fibers.

[0015] The cellulose fiber includes at least one of tencel cellulose, viscose fiber, modal fiber, cotton fiber, cupro fiber, hemp fiber, and acetate fiber; the non-cellulose fiber is an alkali-resistant non-cellulose fiber, including at least one of nylon fiber, vinylon fiber, and polypropylene fiber.

[0016] The base fabric in step (1) is at least one of spunlace nonwoven fabric, needle-punched nonwoven fabric, hem nonwoven fabric, knitted fabric, and woven fabric.

[0017] The concentration of the potassium chloride solution in step (1) is 20wt%.

[0018] The mass ratio of the base fabric to the potassium chloride solution in step (1) is 1:5-15.

[0019] The temperature of the heating treatment in step (1) is 50° C. and the time is 1 hour.

[0020] The pressure of the rolling mill in step (1) is 0.5 MPa.

[0021] The mass ratio of sodium hydroxide to water in the sodium hydroxide solution of step (2) is 1-10:50.

[0022] The mass ratio of the sodium hydroxide solution in step (2) to the base fabric in step (1) is 4-16:1.

[0023] The reaction temperature in step (2) is 25-60°C and the reaction time is 30-180 min.

[0024] The solute of the etherification solution in step (3) is at least one of ethylene oxide, chloroacetic acid, propylene oxide and methyl chloride; the solvent is at least one of water and ethanol; and the mass ratio of the solute to the solvent is 1-5:20.

[0025] The mass ratio of the etherification solution in step (3) to the base fabric in step (1) is 3-10:1.

[0026] The microwave-assisted power of step (3) is 100-300 W; the reaction temperature is 40-70 °C; and the reaction time is 2-10 min.

[0027] The solute of the crosslinker solution in step (4) is at least one of citric acid, ethylene glycol diglycidyl ether, epichlorohydrin, tartaric acid, and genipin; the solvent is water; and the content of the solute in the crosslinker solution is 10-40wt%.

[0028] The mass ratio of the cross-linking agent solution in step (4) to the base fabric in step (1) is 1-10:1.

[0029] The reaction temperature in step (4) is 70-110°C and the reaction time is 30-120 minutes.

[0030] The drying in step (4) is one of drying and freeze drying.

[0031] The cross-linked cellulose-based dry absorbent fabric prepared by the above method.

[0032] Application of the cross-linked cellulose-based dry absorbent fabric in wound dressing materials.

[0033] The application is specifically as follows: placing the cross-linked cellulose-based dry absorbent fabric in water to achieve water absorption equilibrium to obtain cross-linked cellulose-based hydrogel fibers; and using the cross-linked cellulose-based hydrogel fibers as wound dressings.

[0034] Compared with the prior art, the present invention has the following advantages and beneficial effects: The present invention solves the problems of uneven cellulose etherification, long reaction time, etc. through microwave-assisted etherification; cross-linking treatment with citric acid is used to increase the intermolecular force of the hydrogel fiber dressing, solving the problems of poor mechanical properties and low liquid retention rate of the cellulose-based cloth. In addition, the present invention has a simple preparation process, controllable performance, and is easy to scale up. The dry absorbent fabric of the present invention can form a fibrous hydrogel with good liquid retention capacity, mechanical properties, and transparency after quickly absorbing liquid, and can be applied to various wound repair scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The present invention is a flow chart of a method for preparing a cross-linked cellulose-based dry absorbent fabric according to an embodiment of the present invention. DETAILED DESCRIPTION

[0036] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0037] Unless otherwise specified, the reagents used in the examples can be purchased from the market.

[0038] The tensile properties test method of the products obtained in Examples 1-12 and Comparative Examples 1-2 refers to Part 1: Determination of breaking strength and elongation at break (strip method) in GBT3923.1-2013 "Tensile Properties of Textile Fabrics".

[0039] Comparative Example 1 An untreated spunlace nonwoven fabric (100 wt % Tencel fiber) was used as a comparative example.

[0040] Performance Testing: The dry cloth breaking strength of the product obtained in this example is 160 N; the water absorption rate is 7 times.

[0041] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing, and the breaking strength of the wet cloth was 80 N; after centrifugation at 1000 rpm for 5 min, it could retain water twice the mass of the dry cloth; the skin-adhering time was 20 minutes; and it was opaque.

[0042] Comparative Example 2 Step 1: immerse 100 g of spunlace nonwoven fabric (100 wt% Tencel fiber) as a base fabric in 1000 g of 20 wt.% potassium chloride solution to ensure that the base fabric is completely soaked, and treat at 50° C. for 1 hour to obtain a treated sample; Step 2: Wash the treated samples with water and control the water content of the samples to 50 wt% by rolling (pressure 0.5 MPa); Step 3, immersing the sample in 1000 g of sodium hydroxide solution, wherein the mass ratio of sodium hydroxide to water is 1:9, and reacting at 40°C for 50 minutes to obtain an alkalized sample; Step 4: add 500 g of chloroacetic acid solution (chloroacetic acid and ethanol are mixed in a mass ratio of 1:9) to the alkalized sample, and react at 55° C. with a microwave power of 230 W for 5 minutes to obtain an etherified sample; Step 5, washing the sample with water, and freeze-drying the sample to obtain the dry absorbent fabric.

[0043] Performance Testing: The dry cloth breaking strength of the product obtained in this example is 74 N; the water absorption rate is 16 times.

[0044] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing and the breaking strength of the wet cloth was 41 N. After centrifugation at 1000 rpm for 5 min, it could retain 10 times the mass of the dry cloth in water. The skin-adhering time was 160 minutes. The transparency at 600 nm was 93%.

[0045] Example 1 Step 1: immerse 100 g of spunlace nonwoven fabric (100 wt% Tencel fiber) as a base fabric in 1000 g of 20 wt.% potassium chloride solution to ensure that the base fabric is completely soaked, and treat at 50° C. for 1 hour to obtain a treated sample; Step 2: Wash the treated samples with water and control the water content of the samples to 50 wt% by rolling (pressure 0.5 MPa); Step 3, immersing the sample in 1000 g of sodium hydroxide solution, wherein the mass ratio of sodium hydroxide to water is 1:9, and reacting at 40°C for 50 minutes to obtain an alkalized sample; Step 4: add 500 g of chloroacetic acid solution (chloroacetic acid and ethanol are mixed in a mass ratio of 1:9) to the alkalized sample, and react at 55°C with a microwave power of 230 W for 5 minutes, wash the product with water, and obtain an etherified sample; Step 5, adding 100 g of 20 wt.% citric acid / water solution to the etherified sample, and sealing the sample and placing it at 80° C. for reaction for 60 minutes; Step six, washing the sample with water, and freeze-drying the sample to obtain the dry absorbent fabric.

[0046] Performance Testing: The dry cloth breaking strength of the product obtained in this example is 90 N; the water absorption rate is 23 times.

[0047] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing, and the breaking strength of the wet cloth was 48 N; after centrifugation at 1000 rpm for 5 min, it could retain 13 times the mass of the dry cloth in water; the skin-adhering time was 240 minutes; and the transparency at 600 nm was 93%.

[0048] Example 2 Step 1: immerse 100 g of spunlace nonwoven fabric (100 wt% Tencel fiber) as a base fabric in 1000 g of 20 wt.% potassium chloride solution to ensure that the base fabric is completely soaked, and treat at 50° C. for 1 hour to obtain a treated sample; Step 2: Wash the treated samples with water and control the water content of the samples to 50 wt% by rolling (pressure 0.5 MPa); Step 3, immersing the sample in 1000 g of sodium hydroxide solution, wherein the mass ratio of sodium hydroxide to water is 1:19, and reacting at 40°C for 50 minutes to obtain an alkalized sample; Step 4: add 500 g of ethylene oxide solution (ethylene oxide and ethanol are mixed in a mass ratio of 1:20) to the alkalized sample, and react at 55°C with a microwave power of 230 W for 5 minutes, wash the product with water, and obtain an etherified sample; Step 5, adding 100 g of 20 wt.% citric acid / water solution to the etherified sample, and sealing the sample and placing it at 95°C for reaction for 60 minutes; Step six, washing the sample with water, and freeze-drying the sample to obtain the dry absorbent fabric.

[0049] Performance Testing: The dry cloth breaking strength of the product obtained in this example is 110 N; the water absorption rate is 17 times.

[0050] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing, and the breaking strength of the wet cloth was 60 N; after centrifugation at 1000 rpm for 5 min, it could retain 12 times the mass of the dry cloth in water; the skin-attaching time was 210 minutes; and the transparency at 600 nm was 95%.

[0051] Example 3 Step 1: immerse 100 g of spunlace nonwoven fabric (100 wt% Tencel fiber) as a base fabric in 1000 g of 20 wt.% potassium chloride solution to ensure that the base fabric is completely soaked, and treat at 50° C. for 1 hour to obtain a treated sample; Step 2: Wash the treated samples with water and control the water content of the samples to 50 wt% by rolling (pressure 0.5 MPa); Step 3, immersing the sample in 1000 g of sodium hydroxide solution, wherein the mass ratio of potassium hydroxide to water is 1:9, and reacting at 40°C for 50 minutes to obtain an alkalized sample; Step 4: add 500 g of chloroacetic acid solution (chloroacetic acid and ethanol are mixed in a mass ratio of 1:9) to the alkalized sample, and react at 65°C with a microwave power of 230 W for 5 minutes, wash the product with water, and obtain an etherified sample; Step 5, adding 100 g of 20 wt.% citric acid / water solution to the etherified sample, and sealing the sample and placing it at 80°C for reaction for 60 minutes; Step six, washing the sample with water, and freeze-drying the sample to obtain the dry absorbent fabric.

[0052] Performance Testing: The dry cloth breaking strength of the product obtained in this example is 87 N; the water absorption ratio is 29 times.

[0053] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing, and the breaking strength of the wet cloth was 47 N; after centrifugation at 1000 rpm for 5 min, it could retain 15 times the mass of the dry cloth in water; the skin-attaching time was 260 minutes; and the transparency at 600 nm was 96%.

[0054] Example 4 Step 1: immerse 100 g of spunlace nonwoven fabric (100 wt% Tencel fiber) as a base fabric in 1000 g of 20 wt.% potassium chloride solution to ensure that the base fabric is completely soaked, and treat at 50° C. for 1 hour to obtain a treated sample; Step 2: Wash the treated samples with water and control the water content of the samples to 50 wt% by rolling (pressure 0.5 MPa); Step 3, immersing the sample in 1000 g of sodium hydroxide solution, wherein the mass ratio of sodium hydroxide to water is 1:9, and reacting at 50° C. for 30 minutes to obtain an alkalized sample; Step 4: add 500 g of chloroacetic acid solution (chloroacetic acid and ethanol are mixed in a mass ratio of 1:9) to the alkalized sample, and react at 55°C with a microwave power of 230 W for 5 minutes, wash the product with water, and obtain an etherified sample; Step 5, adding 100 g of 40 wt.% citric acid / water solution to the etherified sample, and sealing the sample and placing it at 80° C. for reaction for 60 minutes; Step six, washing the sample with water, and freeze-drying the sample to obtain the dry absorbent fabric.

[0055] Performance Testing: The dry cloth breaking strength of the product obtained in this example is 100 N; the water absorption rate is 20 times.

[0056] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing and the breaking strength of the wet cloth was 53 N. After centrifugation at 1000 rpm for 5 min, it could retain 14 times the mass of the dry cloth in water. The skin adhesion time was 270 minutes. The transparency at 600 nm was 94%.

[0057] Example 5 Step 1: immerse 100 g of spunlace nonwoven fabric (100 wt% Tencel fiber) as a base fabric in 1000 g of 20 wt.% potassium chloride solution to ensure that the base fabric is completely soaked, and treat at 50° C. for 1 hour to obtain a treated sample; Step 2: Wash the treated samples with water and control the water content of the samples to 50 wt% by rolling (pressure 0.5 MPa); Step 3, immersing the sample in 1000 g of sodium hydroxide solution, wherein the mass ratio of sodium hydroxide to water is 1:9, and reacting at 50° C. for 30 minutes to obtain an alkalized sample; Step 4: add 500 g of chloroacetic acid solution (chloroacetic acid and ethanol are mixed in a mass ratio of 1:9) to the alkalized sample, and react at 55°C with a microwave power of 230 W for 5 minutes, wash the product with water, and obtain an etherified sample; Step 5, adding 100 g of 20 wt.% citric acid / water solution to the etherified sample, and sealing the sample and placing it at 70° C. for reaction for 30 minutes; Step six, washing the sample with water, and freeze-drying the sample to obtain the dry absorbent fabric.

[0058] Performance Testing: The dry cloth breaking strength of the product obtained in this example is 82 N; the water absorption rate is 28 times.

[0059] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing, and the breaking strength of the wet cloth was 45 N; after centrifugation at 1000 rpm for 5 min, it could retain 15 times the mass of the dry cloth in water; the skin-attaching time was 230 minutes; and the transparency at 600 nm was 95%.

[0060] Example 6 Step 1: immerse 100 g of spunlace nonwoven fabric (100 wt% Tencel fiber) as a base fabric in 1000 g of 20 wt.% potassium chloride solution to ensure that the base fabric is completely soaked, and treat at 50° C. for 1 hour to obtain a treated sample; Step 2: Wash the treated samples with water and control the water content of the samples to 50 wt% by rolling (pressure 0.5 MPa); Step 3, immersing the sample in 400 g of sodium hydroxide solution, wherein the mass ratio of potassium hydroxide to water is 1:9, and reacting at 40°C for 50 minutes to obtain an alkalized sample; Step 4: add 500 g of chloroacetic acid solution (chloroacetic acid and ethanol are mixed in a mass ratio of 1:9) to the alkalized sample, and react at 70°C with a microwave power of 100 W for 3 minutes, wash the product with water, and obtain an etherified sample; Step 5, adding 100 g of 20 wt.% citric acid / water solution to the etherified sample, and sealing the sample and placing it at 80° C. for reaction for 60 minutes; Step six, washing the sample with water, and freeze-drying the sample to obtain the dry absorbent fabric.

[0061] Performance Testing: The dry cloth breaking strength of the product obtained in this example is 83 N; the water absorption rate is 29 times.

[0062] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing, and the breaking strength of the wet cloth was 46 N; after centrifugation at 1000 rpm for 5 min, it could retain 15 times the mass of the dry cloth in water; the skin adhesion time was 250 minutes; and the transparency at 600 nm was 96%.

[0063] Example 7 Step 1: immerse 100 g of spunlace nonwoven fabric (100 wt% Tencel fiber) as a base fabric in 1000 g of 20 wt.% potassium chloride solution to ensure that the base fabric is completely soaked, and treat at 50° C. for 1 hour to obtain a treated sample; Step 2: Wash the treated samples with water and control the water content of the samples to 50 wt% by rolling (pressure 0.5 MPa); Step 3, immersing the sample in 1000 g of sodium hydroxide solution, wherein the mass ratio of potassium hydroxide to water is 1:9, and reacting at 25°C for 180 minutes to obtain an alkalized sample; Step 4: add 500 g of chloroacetic acid solution (chloroacetic acid and ethanol are mixed in a mass ratio of 1:9) to the alkalized sample, and react at 55°C with a microwave power of 230 W for 5 minutes, wash the product with water, and obtain an etherified sample; Step 5, adding 100 g of 20 wt.% citric acid / water solution to the etherified sample, and sealing the sample and placing it at 80° C. for reaction for 60 minutes; Step six, washing the sample with water, and freeze-drying the sample to obtain the dry absorbent fabric.

[0064] Performance Testing: The dry cloth breaking strength of the product obtained in this example is 120 N; the water absorption rate is 15 times.

[0065] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing and the breaking strength of the wet cloth was 65 N. After centrifugation at 1000 rpm for 5 min, it could retain 10 times the mass of the dry cloth in water. The skin-adhering time was 200 minutes. The transparency at 600 nm was 90%.

[0066] Example 8 The difference between this embodiment and embodiment 1 is that spunlace nonwoven fabric (100wt% viscose fiber) is selected as the raw material.

[0067] Performance test: Dry cloth breaking strength is 85 N; wet cloth breaking strength is 46 N; water absorption rate is 29 times; it can retain 15 times the water after centrifugation at 1000 rpm for 5 min; skin adhesion time is 280 minutes; transparency at 600 nm is 94%.

[0068] Example 9 The difference between this embodiment and embodiment 1 is that spunlace nonwoven fabric (100wt% modal fiber) is selected as the raw material.

[0069] Performance Testing: The dry cloth breaking strength of the product obtained in this example is 100 N; the water absorption rate is 20 times.

[0070] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing and the breaking strength of the wet cloth was 54 N. After centrifugation at 1000 rpm for 5 min, it could retain 12 times the mass of the dry cloth in water. The skin-adhering time was 240 minutes. The transparency at 600 nm was 92%.

[0071] Example 10 The difference between this embodiment and embodiment 1 is that in step 5, 20 wt.% ethylene glycol diglycidyl ether / water solution is selected as the cross-linking agent.

[0072] Performance test: Dry cloth breaking strength is 90 N; wet cloth breaking strength is 48 N; water absorption rate is 25 times; it can retain 13 times the water after centrifugation at 1000 rpm for 5 min; skin adhesion time is 230 minutes; transparency at 600 nm is 95%.

[0073] Embodiment 11 The difference between this embodiment and embodiment 1 is that the base fabric is a spunlace non-woven fabric (60wt% viscose fiber and 40wt% nylon fiber).

[0074] Performance test: Dry cloth breaking strength is 130 N; wet cloth breaking strength is 70 N; water absorption rate is 22 times; it can retain 13 times the water after centrifugation at 1000 rpm for 5 min; skin adhesion time is 200 minutes; transparency at 600 nm is 94%.

[0075] Example 12 The difference between this embodiment and embodiment 1 is that the base fabric is a spunlace non-woven fabric (80wt% Tencel fiber and 20wt% polypropylene fiber).

[0076] Performance Testing: The dry cloth breaking strength of the product obtained in this example is 110 N; the water absorption rate is 19 times.

[0077] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing and the breaking strength of the wet cloth was 60 N. After centrifugation at 1000 rpm for 5 min, it could retain 11 times the mass of the dry cloth in water. The skin-adhering time was 230 minutes. The transparency at 600 nm was 91%.

[0078] The test results of the finished products of the above embodiment show that: for a gram weight ≥ 35 g / m 2 According to the test method in GBT3923.1-2013 "Tensile Properties of Textile Fabrics", the cross-linked cellulose base fabric (Examples 1-12) has a dry cloth breaking strength of ≥ 80N; a wet cloth breaking strength of ≥ 45N; compared with the 7-fold water absorption rate of the untreated 100% Tencel spunlace non-woven fabric in Comparative Example 1, the non-woven fabric treated by the present invention (Examples 1-12) can absorb 15-30 times of water; it has good water retention capacity and can still retain 10-15 times of water after centrifugation at 1000 rpm for 5 minutes. The base fabric obtained after the treatment of the present invention is softer after water absorption balance, and the skin-attaching time is extended by 10 to 15 times; the transparency at 600 nm is >90%, so the healing of the wound can be observed without uncovering the dressing, avoiding the secondary damage to the wound surface that may occur when checking the wound.

[0079] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a cross-linked cellulose-based dry absorbent fabric, characterized in that: The following steps are involved: (1) soaking the base fabric in a potassium chloride solution, heating it, washing it, and rolling it until the water content is 50wt%-90wt%, to obtain sample a; (2) soaking sample a in a sodium hydroxide solution to react and obtain an alkalized sample b; (3) adding an etherification solution to the alkalized sample b, reacting under microwave assistance, and washing to obtain an etherified sample c; (4) The etherified sample c is immersed in a crosslinking agent solution to react, and the obtained product is washed and dried to obtain a crosslinked cellulose-based dry absorbent fabric.

2. The method for preparing the cross-linked cellulose-based dry absorbent fabric according to claim 1, characterized in that: The base fabric in step (1) comprises, by mass percentage, 60%-100% cellulose fibers and 0%-40% non-cellulose fibers; The cellulose fiber includes at least one of tencel cellulose, viscose fiber, modal fiber, cotton fiber, cuprammonium fiber, hemp fiber, and acetate fiber; the non-cellulose fiber is an alkali-resistant non-cellulose fiber, including at least one of nylon fiber, vinylon fiber, and polypropylene fiber; The base fabric in step (1) is at least one of spunlace nonwoven fabric, needle-punched nonwoven fabric, hem nonwoven fabric, knitted fabric, and woven fabric.

3. The method for preparing the cross-linked cellulose-based dry absorbent fabric according to claim 1, characterized in that: The concentration of the potassium chloride solution in step (1) is 20wt%; The mass ratio of the base fabric to the potassium chloride solution in step (1) is 1:5-15; The temperature of the heating treatment in step (1) is 50°C and the time is 1 hour; The pressure of the rolling mill in step (1) is 0.5 MPa.

4. The method for preparing the cross-linked cellulose-based dry absorbent fabric according to claim 1, characterized in that: The mass ratio of sodium hydroxide to water in the sodium hydroxide solution of step (2) is 1-10:50; The mass ratio of the sodium hydroxide solution in step (2) to the base fabric in step (1) is 4-16:1; The reaction temperature in step (2) is 25-60°C and the reaction time is 30-180 min.

5. The method for preparing the cross-linked cellulose-based dry absorbent fabric according to claim 1, characterized in that: The solute of the etherification solution in step (3) is at least one of ethylene oxide, chloroacetic acid, propylene oxide and methyl chloride; the solvent is at least one of water and ethanol; the mass ratio of the solute to the solvent is 1-5:20; The mass ratio of the etherification solution in step (3) to the base fabric in step (1) is 3-10:

1.

6. The method for preparing the cross-linked cellulose-based dry absorbent fabric according to claim 1, characterized in that: The microwave-assisted power of step (3) is 100-300 W; the reaction temperature is 40-70 °C; and the reaction time is 2-10 min.

7. The method for preparing the cross-linked cellulose-based dry absorbent fabric according to claim 1, characterized in that: The solute of the crosslinker solution in step (4) is at least one of citric acid, ethylene glycol diglycidyl ether, epichlorohydrin, tartaric acid, and genipin; the solvent is water; and the content of the solute in the crosslinker solution is 10-40wt%.

8. The method for preparing the cross-linked cellulose-based dry absorbent fabric according to claim 1, characterized in that: The mass ratio of the cross-linking agent solution in step (4) to the base fabric in step (1) is 1-10:1; The reaction temperature in step (4) is 70-110°C and the reaction time is 30-120min.

9. The cross-linked cellulose-based dry absorbent fabric prepared by the method according to any one of claims 1 to 8.

10. Use of the cross-linked cellulose-based dry absorbent fabric according to claim 9 in wound dressing materials.

Citation Information

Patent Citations

  • High-water-absorption fiber and preparation method thereof

    CN113818232A

  • Preparation method of cellulose fiber-containing gelatinized spunlace non-woven fabric

    CN114645456A

  • Preparation method of skin-friendly composite fiber with high water absorbability

    CN117661325A

  • Polymer hydrogels and methods of preparation thereof

    US20100234233A1